The new Bartonella ancashi to cause the Peruvian wart: Does Koch’s postulates? - Salinas-Flores, David (2014)
Although most of the bacteria that cause disease in humans adapt to the Kochs postulates. Kochs postulates as the first model had to Bacillus anthracis, the bacterium that was first shown to be the cause of an infectious disease, whose life cycle was discovered by Koch. Oroya fever and Peruvian wart on one disease. Peruvian wart is an infection with a characteristic clinical pattern, caused by Bartonella bacilliformis. Recent published studies awarded as the cause of a new Peruvian wart bartonella, the Candidatus Bartonella ancashi. Analyzing research, the proposed causality of B. ancashi is based only on observational evidence: the association of the new bartonella in one patient with a clinical pattern similar to the wart Peruvian and the origin of the patient from an endemic area. With the new B. ancashi has not been investigated whether or not it meets all of Kochs postulates, still lack experimental reproduction of Peruvian wart animals to contend with more proven that causes the Peruvian wart. Observational evidence does not necessarily determine causality. An association between a specific infection and a particular infectious agent does not means that the agent cause disease. Science needs to base its conclusions on the best available evidence and reasoning.